Hydrodynamic spreading in 2 & 3-streams flow. - Tan, Kian Chong. (2009)
This project investigates the effects of several physical factors on hydrodynamic focusing in two and three streams flow. Hydrodynamic focusing is the technique of controlling the width of a fluid of interest with the help of another fluid. This paper examines how streams of fluid, which flow side by side and share a liquid interface, can be subjected to widening or narrowing by controlling appropriate parameters. One of the applications of hydrodynamic focusing is flow cytometry, where the effect of narrowing of the central flow (sample fluid) creates a single file of particles (eg. cells). Under the right conditions, mixing between the sample flow and the surrounding fluid flow (sheath flow) can be kept to a minimal and analysis of the sample fluid can be made. Parameters such as flow rate ratio, dynamic viscosity ratio and diffusion coefficients of the fluids affect the width of the sample flow and the interfacial position. Experiments were first carried out to investigate several crucial parameters on chips made of Polydimethylsiloxane with suitable structures while COMSOL Multiphysics software was used for numerical simulations of the flows. The steady state flow of fluids is governed by Naver-Stokes equations while diffusion equation determines the diffusion flux and focusing effect. The designs of hydrodynamic focusing devices used in this project consist of two or three inlet streams that merge into one main channel.